The effects of a single bout of exercise on motor memory interference in the trained and untrained hemisphere - Lauber, B.; Taube, W.; Gollhofer, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Aim: Increasing evidence suggests that cardiovascular exercise has positive effects on motor memory consolidation. In this study, we investigated whether a single session of high-intensity interval training mitigates the effects of practising an interfering motor task. Furthermore, learning and interference effects were assessed in the actively trained and untrained limb, as it is known that unilateral motor learning can cause bilateral adaptations. Methods: A total of 30 subjects were divided into three groups and equally distributed based on their fitness level determined during a graded VO2max test 1 week prior to the experiment. Subsequently, subjects performed a ballistic training comprised of 45 contractions aiming to increased their rate of force development. This was followed by a single session of highintensity interval training (4x4min at 75% of the max workload obtained during the VO2max test) either before (Group1) or after (Group 2) practising a interfering accuracy task (visuomotor tracking). The control group (Group 3) did not participate in the HIIT, but rested instead. Performance in the ballistic task was tested before and after the ballistic training, after the exercise and practise of the accuracy task, and 24 hours later. Results: After ballistic training, all groups showed comparable increases in performance in the trained (98.1 ± 30. 5%) and untrained limb (71.5 ± 25.7%). Despite the practise of the accuracy task, Group 1 (-4.9 ± 6.11%, p = 0.39) maintained their ballistic task performance after the high-intensity interval training, whereas Groups 2 (-21.57 ± 5.80%, p = 0.01) and 3 (-13.69 ± 5.28%, p = 0.01) showed significant interference effects. After 24 hours, Group 1 still did not show any interference effects. Group 2 counteracted the interference, resulting in increased in ballistic task performance (+43.94 ± 12.80%, p < 0.01) so Group 1 (142.23 ± 46.21%) and Group 2 (142.07 ± 29.45%) had significantly higher overall ballistic learning rates compared to Group 3 (47.38 ± 21.24%). The results were similar in the trained and untrained limb. Conclusion: A single session of cardiovascular exercise can prevent motor interference in the trained and untrained hemisphere, irrespective of whether it is performed before or after the interfering motor task.